Dessy Rachma's digital illustrations: The creative process and formal analyses - Azizah, Anie Qotul; Ambarwati, Dwi Retno Sri (Universitas Negeri Yogyakarta, 2024)
This research aims to 1) describe the creative process of Dessy Rachma's digital illustration work, 2) describe Dessy Rachma's artistic journey, and 3) describe the marketing strategy for Dessy Rachma's work. This qualitative research uses descriptive methods to describe the results in detail. So, the final result of this research is an analysis and discussion of the results based on several art theories. Data sources were collected using triangulation techniques: observation, interviews, and documentation. Moreover, the validity of the data will be tested using a member check (checking research data with the data provider). The results of this research show that: 1) Dessy's creative process in working uses digital media and techniques, and the characteristics of the work highlighted are themes about feminism with the use of neon colours such as in cyber art style; 2) Dessy's artistic journey started when she was in college, continued until she was in graduate school, and now she has marketed many of her digital works on the Crypto Ar market; 3) The marketing strategy for Dessy's work is carried out by marketing her work on a platform from Crypto Art called Teia. art which Dessy not only uses as a marketing medium but also as a place for archiving her work and as a medium to increase her branding.